In Search of Effective Disability Policy Comparing the Developments and Outcomes of the Dutch and Danish Disability Policies - Hogelund, Jan (Changing Welfare States, 2003)
In Search of Effective Disability Policy examines the potentials of two very different strategies of integrating disabled people into the working life. In the Netherlands employers have great responsi-bility for the integration. In contrast employers have limited responsibility in the Danish strategy, where public authorities are crucial. This book finds that there are virtues and drawbacks of both strategies. While the Dutch policy promotes work-retention of sick-listed workers, it hampers the labour market entry of non-employed disabled people. This is so because employers avoid hiring disabled people as future work-disability inflicts costs upon employers. This is not the case in Denmark. But here too many workers with health problems lose their labour market attachment because employers are allowed to dismiss them and as public reintegration measures do not work as intended. Consequently, an effective disability policy should demand neither too little nor too much of employers. By combing macro-level analyses with empirical analyses at the micro-level this book distinguishes itself from most other studies in the field.